Datum definition for geodetic vertical velocity field derived from GNSS observations: a case study in western and southern Turkey - Erkoc, M. H.; Dogan, U. (IST NAZIONALE DI OCEANOGRAFIA E DI GEOFISICA, 2023)
This study aims to determine the datum definition for the geodetic vertical velocity field derived from temporary and continuous GNSS observations. The observations have been analysed to investigate how the effect of vertical velocity for GNSS stations depends on the reference station selection. For this purpose, a network consisting of 26 GNSS stations has been designed. The GNSS observations have been processed using Bernese GNSS software v5.2 according to the different strategies. The strategies have been generated from ten different datum definitions of one to ten continuous GNSS stations within the IGS network in the Eurasia region, which is thought to be the least affected by tectonic movements. The vertical velocities of our solution derived from four reference stations concur within 0.4 mm/yr with those of the IGS/EUREF/NGL solution. It has been determined that the vertical velocities obtained based on the four reference stations proposed within the scope of the study are equal to the vertical velocities obtained from the ten stations distributed over the European region. The usability of these outcomes has been investigated in the studies to be carried out on Turkey's west and south coasts.
Keywords: GNSS; time series; datum definition; vertical velocity; RELATIVE POSITIONS; MARMARA REGION; GPS; ACCURACY; DEFORMATION; TOOL; Geochemistry & Geophysics